Foreign trade relations of the Peru Republic and Russia: history and development prospects - O. N. Zhilkin; G. W. P. Chavarry (Вестник университета, 2022)
The article analyses the historical aspects and prospects for the development of foreign trade relations between Peru and Russia. The dynamics of RussianPeruvian diplomatic relations was studied, the most significant periods of these relations were highlighted, the crisis periods that affected cooperation between countries, including the Second Pacific War (1879−1884) were identified, and the collapse of the USSR. The most fruitful period in the history of Russian-Peruvian relations is marked by the beginning of the “most-favoured-nation” regime, established in 1969 after the signing of the Trade Agreement by the parties. The key aspects of the current state of trade cooperation between Peru and Russia are highlighted. The intensification of trade cooperation in the modern period occurred after the meeting of the presidents of Russia and Peru in 2008 at the Asia-Pacific Economic Cooperation summit in Lima. The commodity structure of trade relations between Peru and Russia is considered. It is suggested that the priority tasks for the further active development of Russian-Peruvian cooperation can be considered the increase and diversification of trade, the growth of mutual investment, and the signing of a bilateral free trade agreement. The methodological basis of the research includes general scientific methods: historical-legal, structural-functional, comparative-legal, formal-legal, statistical. The information work was compiled scientific literature, monographs, regulatory documents, and reference materials that demonstrate the functioning of foreign economic activity, including between Russia and Peru.